Characteristics of Beaver Ponds and Landforms Induced by Beaver Activity, S Part of the Tuchola Pinewoods, Poland - Rurek, Mirosław (Water (Basel), 2021)
Currently, there are only two species of beavers described—the North American beaver (Castor canadensis) and Eurasian beaver (Castor fiber). Their natural habitats are confined to the northern hemisphere but instances of beaver introduction to regions of the world they do not normally inhabit have also been recorded. The activity of beavers leads to changes in the natural environment linked to hydrological and geomorphological and plant cover transformations. Beavers live in natural and artificial water reservoirs and rivers. If the water level in the river is too low, they build dams to create a comfortable living environment. This paper aims to present changes in the relief of the valley inhabited by beavers in which sediments accumulate. During the field study, detailed measurements of dams and of the spatial range of beaver ponds were made, and the thickness and spatial distribution of accumulated sediments were determined. In addition, measurements of geomorphological forms in beaver ponds were also made. The samples of sediments were subject to grain-size distribution analysis, the results of which allowed calculating sediment parameters. Beavers appeared in the Gajdówka valley in the southern part of the Tuchola Forest (Poland) in 2008. In 2008–2011 they built 17 beaver dams that impounded ponds. The beaver ponds and beaver dams were of different sizes. They either flooded the whole flat bottom of the valley or only raised the level of water in the riverbed. A characteristic feature of beaver ponds is that they capture sediments. Different landforms were created in the course of the formation and disappearance of beaver ponds. It was established that these include alluvial fans, levees, sand shadow dunes and microterraces formed by deposition and erosion. They do not occur in all ponds. Points at which mineral sediments are supplied to the watercourse, including beaver burrows and erosion hollows, are presented together with the points at which sediments are transferred from ponds upstream to ponds downstream the watercourse. Beaver activity during valley colonization shows changes in the landscape caused by their presence and in particular their impact on the relief and deposition of sediments. Analysis of contemporary changes in the morphology of the Gajdówka Valley leads to the conclusion that beaver activity has had an intense impact on the terrain relief of the valley inhabited by beavers.